The Logic Of Phallus And Object Of Desire: Rethinking ‘Masculinities’ in Literary Works of Contemporary Indonesian Woman Writers - Achmad Fawaid (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The recent studies commonly pointed out that literary works of contemporary Indonesian women writers have coined feminist ideology. However, the study on reading these writers in ‘masculine’ perspective is rarely given. This study amins to analyze the works of two important Indonesian women writers, Ayu Utami and Djenar Maesa Ayu to demonstrate the inadequate definition of labels 'masculine' and 'feminine’ as binary opposition between male and female for explaining a much more fundamental problem: desire. This study concluded that first, the short stories of Ayu Utami and Djenar Maesa Utami demonstrate—in Connell's terminology—the master signifier or—in Lacan's terminology—phallic desire towards male, meaning that, instead of being regarded as "feminist champions," they are possible to be considered as "masculine without an object." Second, concept of "masculine without an object" is plural and splitted. Although neither Djenar nor Utami can avoid the fact that they are female, both of them were born into a multifaceted environment, an environment that strove to break down an essentialist barrier between male and female.